Contribution to the genus Plutomurus Yosii (Collembola, Tomoceridae): notes on the morphology of Plutomurus carpaticus Rusek & Weiner and P. unidentatus (Börner) - Barjadze, Shalva; Kováč, Ľubomír; Parimuchová, Andrea (Zootaxa, 2020)
In two European species of the genus Plutomurus Yosii, P. carpaticus Rusek & Weiner and P. unidentatus (Börner), several diagnostic morphological characters are specified and illustrated: body chaetotaxy, number of internal spine-like chaetae on tibiotarsi and number of teeth on claw. The contribution is based on the study of type specimens of both species and specimens of other populations of their distribution ranges. The numerous specimens of the genus Plutomurus collected recently in the Western Carpathian caves are the most similar to P. carpaticus, but differ in macrochaetotaxy and may represent a new species. Three types of macrochaetae on thorax and abdomen of Plutomurus congeners from the Europe and Caucasus are defined. Identification key to European Plutomurus species is provided.